PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE STAD TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS V - Pane, Fhazizah Dewi; Nurmayani, Nurmayani; Simanjuntak, Sorta; Manurung, Imelda Free; Prawijaya, Septian (Jurnal Merah Putih Sekolah Dasar, 2024)
Mathematics lessons in elementary schools tend to be less than optimal, this is due to the choice of learning models used which are not student-centred. This attracted the attention of researchers so that they could determine the effect of the STAD type cooperative learning model on the mathematics learning outcomes of class V students at SD Negeri 104607 Sei Rotan T.A 2023/2024. This research is quantitative research using quasi-experimental research. The instrument used is a multiple choice test with a total of 20 questions. Research findings say that learning outcomes by applying the STAD type cooperative learning model get an average score of 82.10, while conventional learning outcomes get an average score of 68.42. Based on the results of hypothesis testing using the t-test, it shows that at the 0.05 significance level it was found that ð‘¡â„Žð‘–ð‘¡ð‘¢ð‘›ð‘” > ð‘¡ð‘¡ð‘Žð‘ð‘’ð‘™ (5.412 > 1.684), then H0 was rejected and Ha was accepted, meaning that there was an influence on the learning outcomes of students who were taught using the STAD Type Cooperative learning model. (Student Teams Achievement Division).